PROSES MORFOFONEMIK DALAM BAHASA INGGRIS DAN BAHASA GORONTALO (SUATU ANALISIS KONTRASTIF) - Dimyati, Farida Kusuma (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€œMorphophonemic Process in English and Gorontalo Language: a Contrastive Analysisâ€ aims at identifying, analyzing and describing the morphophonemic processes and finding out the similarities and the differences of morphophonemic processes in English and Gorontalo language by using of Crystalâ€™s (2008) and Nidaâ€™s (1949) theory. The English data were collected from several English textbooks. Some of them areA Course in Modern Linguistics(1968) by Hockett,Zeitchrift fÃ¼r Anglistik und Amerikanistik (1969) by Lehnert,Introducing English Linguistics (2009) by Meyer, etc. and the data of Gorontalo language were collected frombooks such asMorfologi dan Sintaksis Bahasa Gorontalo (1988) by Alitu et all.,Kamus Bahasa Gorontalo â€“ Indonesia (2001) by Pateda, and Tata Bahasa sederhana Bahasa Gorontalo (2006) by Pateda and Pulubuhu and fivenative speakers at the age of 35-75 years old in Gorontalo. The results of this research shows that in morphophonemic process of English and Gorontalo language have some similarities anddifferences. The similarities are that both languages have kinds of morphophonemic processes. English has seven kinds of morphophonemic processes, they are assimilation, dissimilation, reduction of clusters, loss of consonant phonemes, loss of vowel phonemes, palatalization, and nasalization whereas in Gorontalo language six kinds of them found.The difference is no palatalization found in Gorontalo Language. Other similarities anddifferences are in dissimilation. English has six kinds of dissimilations, they are progressive, regressive, contiguous phonemes, noncontiguous phonemes, point of articulation, and manner of articulation whereas Gorontalo language has only five kinds of dissimilations and doesnâ€™t have contiguous phonemes. Â  Keywords: Morphophonemic Process, English and Gorontalo Language, Contrastive Analysis.